APC is required for muscle stem cell proliferation and skeletal muscle tissue repair - Parisi, Alice (J Cell Biol, 2015)
The tumor suppressor adenomatous polyposis coli (APC) is a crucial regulator of many stem cell types. In constantly cycling stem cells of fast turnover tissues, APC loss results in the constitutive activation of a Wnt target gene program that massively increases proliferation and leads to malignant transformation. However, APC function in skeletal muscle, a tissue with a low turnover rate, has never been investigated. Here we show that conditional genetic disruption of APC in adult muscle stem cells results in the abrogation of adult muscle regenerative potential. We demonstrate that APC removal in adult muscle stem cells abolishes cell cycle entry and leads to cell death. By using double knockout strategies, we further prove that this phenotype is attributable to overactivation of β-catenin signaling. Our results demonstrate that in muscle stem cells, APC dampens canonical Wnt signaling to allow cell cycle progression and radically diverge from previous observations concerning stem cells in actively self-renewing tissues.